BIII 5‐Arylsubporphyrins and BIII Subporphine. Issue 72 (4th May 2018) - Kise, Koki; Yoshida, Kota; Kotani, Ryota; Shimizu, Daiki; Osuka, Atsuhiro
Abstract: Boron(III) 5‐arylsubporphyrins and B III subporphine are promising precursors for functional B III subporphyrins bearing asymmetric meso ‐substituents. Herein, we report the first synthesis of these molecules. Among many aryl acid chlorides examined, 4‐nitrobenzoyl chloride gave B III 5‐(4‐nitrophenyl)subporphyrin in 10 % yield in condensation with triethylamine‐tri‐ N ‐tripyrromethene‐borane. The nitro group of this B III subporphyrin was reduced with NaBH4 to prepare B III 5‐(aminophenyl)subporphyrin, which was converted into B III 5‐phenylsubporphyrin via the corresponding diazonium salt. B III subporphine was synthesized by condensation of triethyl orthoformate with triethylamine‐tri‐ N ‐tripyrromethene‐borane. Progressive removal of meso ‐phenyl substituents leads to continuous changes in the optical properties, whereas the B III subporphine deviates from this trend in some properties. Abstract : Rotational relaxation : B III 5‐arylsubporphyrins and B III subporphine were synthesized for the first time by the condensation reactions of triethylamine‐tri‐ N ‐tripyrromethene‐borane with aryl acid chloride and ethyl orthoformate, respectively. Removal of meso ‐phenyl substituents leads to progressive changes in the optical properties up to B III 5‐arylsubporphyrin but B III subporphine deviates from this trend (see figure).